2021
DOI: 10.1155/2021/6692511
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hepatitis with Elevated Serum IgG4 Levels Have a High Prevalence of Cirrhosis at Diagnosis

Abstract: Background. Some autoimmune hepatitis (AIH) patients have elevated serum IgG4 levels, and the clinical characteristics of such patients are currently incompletely characterized. Aim. To analyze the clinical features and possible pathogenesis of AIH with elevated serum IgG4 levels. Methods. According to their serum IgG4 value, patients were divided into elevated IgG4 (IgG4 > 1.35 g/l) and normal IgG4 (IgG4 ≤ 1.35 g/l) groups. Results. Among the 152 patients included in this study, those in the elevated IgG4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The current study cohort showed a five-year mortality of around 14% without gender predilection (Figure 2). Serum immunoglobulin-4 is associated with higher mortality in patients with autoimmune liver disease, especially in primary sclerosing cholangitis [21,22]. However, its significance in AIH remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The current study cohort showed a five-year mortality of around 14% without gender predilection (Figure 2). Serum immunoglobulin-4 is associated with higher mortality in patients with autoimmune liver disease, especially in primary sclerosing cholangitis [21,22]. However, its significance in AIH remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, cabe destacar que el compromiso pleural puede presentarse de forma aislada o asociado a compromiso de otros órganos, más frecuentemente de origen hepatobiliar, renal, pulmonar y de glándulas salivales 11,12 . En este caso, el paciente se presenta con antecedentes previos de hepatopatía crónica no filiada e insuficiencia renal crónica de causa etiopatogénica poco clara, no pudiéndose descartar su relación con ER-IgG4 en el contexto clínico, serológico y anatomopatológico que se nos plantea 13,14 . Dado que se trata una enfermedad con una gran heterogeneidad clínica, recientemente se han identificado cuatro fenotipos clínicos de ER-IgG4 mediante análisis de clases latentes 11,12 , con el objetivo de ofrecer un marco sistemático que permita facilitar el reconocimiento temprano de la afección, identificar factores de riesgo y desarrollar estrategias de tratamiento personalizadas.…”
Section: Discussionunclassified
“…After a median of 139 mo of long-term observation, the recurrence rate of IgG4-AIH was lower than that of classical AIH. Xue et al [ 15 ] observed 152 patients with AIH. They analyzed 111 patients with AIH in the low IgG4 group (< 135 mg/mL) and 41 patients in the high IgG4 group (> 135 mg/mL) and found that those in the high IgG4 group presented a higher proportion of cirrhosis than those in the low IgG4 group.…”
Section: Discussionmentioning
confidence: 99%